Men's tug-of-war team wearing dressing gowns, S.S. Rotorua, 1935 - Women's Cricket Association (1935)
Left: Lamb, Henry, Peter Haw, Eric Westwood, Mr Lawrence, and Jack.
Title devised by cataloguer.
Condition: Good.
Also available online
Keywords: Women's Cricket Association -- Photographs; Rotorua (Ship) -- Photographs; Ocean Travel -- Photographs